A Study of Some Problems on the Dirichlet Characters (mod q) (Contemporary Mathematics, 2024)
Consider q to be an integer, and χ to be a Dirichlet character (mod q). The main purpose of this paper is using the analytic methods to study some problems related to the Dirichlet character (mod q).
Keywords: Dirichlet character; principal character; primitive character; analytic methods